Anaesthetic challenges and perioperative management of a post renal transplant patient posted for a non transplant surgery- A case report : Case report - Mishra, Dr Roly (British Journal of Healthcare and Medical Research, 2022)
With the advancements in the current health care practices the number of successful renal transplants has increased exponentially.Because of which we see more number of such patients presenting for elective or emergency non-transplant surgery. Authors here would like to discuss a case of a 50 years old male with status post renal transplant suffering from severe ulcerative colitis now posted for Laparoscopic total colectomy and pouch reconstruction.This case report reviews major anaesthetic challenges and successful perioperative management for the organ transplant recipient patient undergoing major non-transplant surgery.